Development of Articulate Storyline-Based Interactive Learning Media to Improve Vocational High School Students’ Learning Outcomes in Basic Accounting Equations - Aura Rizky Iswana Firdausy; Rochmawati Rochmawati (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2026)
This study aims to develop interactive learning media based on Articulate Storyline for the topic of Basic Accounting Equations, evaluate its feasibility, and examine its effectiveness in improving students’ learning outcomes. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The effectiveness test was conducted using a quasi-experimental pretest–posttest control group design involving tenth-grade students of Accounting and Institutional Finance (AKL) at SMK Negeri 4 Surabaya, consisting of 30 students in the experimental group and 30 students in the control group. Data were collected through expert validation sheets, student response questionnaires, and learning outcome tests. Feasibility data were analyzed descriptively using percentage techniques, while learning outcome data were analyzed using normality tests, homogeneity tests, independent samples t-test, N-gain, and effect size. The results showed that the developed media achieved validation scores of 92% from material experts, 90% from language experts, and 96% from media/graphics experts, all categorized as highly feasible. The effectiveness test revealed that the experimental group achieved a higher mean posttest score than the control group, with a statistically significant difference between the two groups. The N-gain value of the experimental group was also higher and supported by a large effect size. In addition, students responded very positively to the use of the media. Therefore, the Articulate Storyline-based interactive learning media is considered highly feasible and effective in supporting the learning of Basic Accounting Equations.